Integrating glacier flow in hydrological modelling for water resources management - Momblanch, Andrea; Shirsat, Tejal; Kulkarni, Anil; Holman, Ian P. (EGU: European Geophysical Union, 2022)
The climate emergency will drive changes in the cryosphere and hydrology of high mountain catchments, with subsequent influences on water resources availability. Process-based hydrological and glaciological models require significant amounts of data which are often unavailable in high mountainous catchments, especially in developing countries, and are unable to explicitly integrate human-induced factors on river flows (Momblanch et al. 2019). This can be overcome by water resources systems models that take a more conceptual approach. However, they currently have limited capability to represent glacier evolution and thus river discharge dynamics, especially in long-term simulations required for climate change impact and adaptation analysis. There is, therefore, a clear need for improved representation of the spatio-temporal response of glaciers within water resources systems models to support the strategic water resources planning and management and ensure future water security.
Abstract only